Addressing the Laboratory Workforce Shortage in Saudi Arabia: Strategies for Recruitment, Retention, and Education - A Qualitative Study - Mohammed Hussain Abdulmohsen Albeladi,; Ahmad Tahir A Al Hamad,; Saeed Hassan H Al Abbad,; Mohammed Khalifah Mohammed Alali,; Aref Ali A Alessa, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This qualitative study aimed to explore strategies for addressing the laboratory workforce shortage in Saudi Arabia, focusing on recruitment, retention, and education. Methods: Semi-structured interviews were conducted with 20 laboratory professionals, including specialists and technicians, working in various healthcare settings across Saudi Arabia. Participants were recruited using purposive sampling, and data were analyzed using thematic analysis. Results: Four main themes emerged from the data: (1) expanding educational programs, (2) enhancing job satisfaction and work environment, (3) promoting public awareness and recognition, and (4) fostering collaboration and partnerships. Participants emphasized the need for increasing the capacity and quality of educational programs, improving working conditions and career advancement opportunities, raising public awareness about the importance of laboratory professionals, and establishing collaborations between educational institutions and healthcare facilities. Conclusion: Addressing the laboratory workforce shortage in Saudi Arabia requires a multifaceted approach that encompasses strategies for recruitment, retention, and education. Policymakers, educational institutions, and healthcare organizations should work together to implement these strategies and ensure a sufficient and competent laboratory workforce to meet the growing healthcare demands in the country.